MIRIZZI’S SYNDROME: AN INTERESTING ON TABLE FINDING - Khalid, Sadaf; Bhatti, Afsar Ali (Journal of Ayub Medical College Abbottabad, 2014)
caused by an extrinsic compression from an impacted stone in the cystic duct or Hartmann’s pouch of the gallbladder. It has been estimated to occur in 0.7-1.8 percent of all cholecystectomies. The preoperative diagnosis of Mirrizi’s syndrome is a not always easy despite the availability of latest advances in the radiological tests which can lead to significant morbidity and bile duct injury. We present the case of a 50-year-old Asian female with Mirizzi’s syndrome who was initially having an impression of cholangiocarcinoma with cholecystitis and cholelithiasis based on radiological findings. Our patient was diagnosed as having Mirizzi’s syndrome on an IV contrast CT scan. Cholecystectomy was performed with a restoration of biliary drainage by placing a t-tube. The on-table findings of the Mirizzi’s syndrome can vary considerably as compared to the preliminary diagnosis based upon the biochemical tests and the radiological studies. The grade of the fistula, the extent of involvement of the biliary channels can only be found out on proper on-table surgical assessment. Keywords: Mirizzi’s syndrome; Cholangiocarcinoma; Obstructive jaundice